Analysis of Economic Policy During the Time of Sultan Jalaludin Akbar in the Mughal Empire - Ramadhani, Ferry; Herman, Sebastian (Universitas Pembangunan Nasional Veteran Jakarta, 2023)
Based on the background and scope as stated above, the researchers identified the problems to be studied in this paper, including the following: What is the background of the policies of the government of Jalalludin Muhammad Akbar in India in 1556-1605 AD and What is the economic policy strategy of Jallaludin Muhammad Akbar in India in 1556-1605 AD, Based on the formulation of the problem above, the objectives to be achieved by researchers in writing this paper are: 1) Assess the role of Jallaludin Muhammd Akbar in carrying out the economic policies of the government of the Mughal Empire in India in 1556-1605 AD In this study the authors used historical research methods. The historical method is the process of examining and critically analyzing past records and legacies (Gottschalk, 1985:32). The historical method has four steps in conducting historical research, namely (1) Heuristics, (2) Historiography. (3) critic, (4) Interpretation Agriculture and Trade Sector the Mughal economic system was based on agriculture and trade. communication between farmers regulated by the government in a good way. Taxation Council (1) high taxes given to high officials of the Mughal Empire, (2) Taxeslow for farmers. Tax collection is usually in the form of land tax and property tax (Ownership of goods) The conclusion in my paper is that regarding King Jalalludin Akbar, his economic policies are closely related to being based on the political and social policies that existed in the Mughal dynasty. poor people do not object to economic policies, but object to other policies, high tolerance with normal taxes makes economic policies run smoothly even though removing the jizyah policy but jalaludin agung can still reach its peak of glory with agriculture and its export trade to various regions